Characteristics of Pan-Cancer Patients With Ultrahigh Tumor Mutation Burden - Yuan, Hong; Ji, Jun; Shi, Min; Shi, Yan; Liu, Jing; Wu, Junwei; Yang, Chen; Xi, Wenqi; Li, Qingyuan; Zhu, Wei; Li, Jingjie; Gong, Xiaoli; et al. (Frontiers in Oncology, 2021)
Background: Tumor mutation burden has been proven to be a good predictor for the efficacy of immunotherapy, especially in patients with hypermutation. However, most research focused on the analysis of hypermutation in individual tumors, and there is a lack of integrated research on the hypermutation across different cancers. This study aimed to characterize hypermutated patients to distinguish between these patients and nonhypermutated patients. Methods: A total of 5,980 tumor samples involving 23 types of solid tumors from the in-house database were included in the study. Based on the cutoff value of tumor mutation burden (TMB), all samples were divided into hypermutated or nonhypermutated groups. Microsatellite instability status, PD-L1 expression and other mutation-related indicators were analyzed. Results: Among the 5,980 tumor samples, 1,164 were selected as samples with hypermutation. Compared with the nonhypermutated group, a significant increase in the mutation rates of DNA mismatch repair genes and polymerase genes was detected in the hypermutated group, and there was an overlap between high TMB and high microsatellite instability or high PD-L1. In addition, we found that EGFR, KRAS and PIK3CA had a high frequency of both single nucleotide variation and copy number variation mutations. These identified mutant genes were enriched in the oncogenic signaling pathway and the DNA damage repair pathway. At the same time, the somatic cell characteristics and distribution of the two groups were significantly different. Conclusions: This study identified genetic and phenotypic characteristics of hypermutated tumors and demonstrated that DNA damage repair is critically involved in hypermutation.